2020
DOI: 10.3390/v12080818
|View full text |Cite
|
Sign up to set email alerts
|

Virus Pathogens in Australian Vineyards with an Emphasis on Shiraz Disease

Abstract: Grapevine viruses are found throughout the viticultural world and have detrimental effects on vine productivity and grape and wine quality. This report provides a comprehensive and up-to-date review on grapevine viruses in Australia with a focus on “Shiraz Disease” (SD) and its two major associated viruses, grapevine virus A (GVA) and grapevine leafroll-associated virus 3 (GLRaV-3). Sensitive grapevine cultivars like Shiraz infected with GVA alone or with a co-infection of a leafroll virus, primarily GLRaV-3, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
37
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 81 publications
2
37
1
Order By: Relevance
“…Depending on the species (variety) of the host and its resistance to the virus, primary diagnosis of the disease and the degree of damage to the plants can be determined [ 24 ]. Unfortunately, viral disease diagnosis using symptoms is more difficult than that for other pathogens due to the fact that several viruses can be present in a host that may alter symptom expression [ 25 ].…”
Section: Methods For Plant Viral Diagnosticmentioning
confidence: 99%
“…Depending on the species (variety) of the host and its resistance to the virus, primary diagnosis of the disease and the degree of damage to the plants can be determined [ 24 ]. Unfortunately, viral disease diagnosis using symptoms is more difficult than that for other pathogens due to the fact that several viruses can be present in a host that may alter symptom expression [ 25 ].…”
Section: Methods For Plant Viral Diagnosticmentioning
confidence: 99%
“…Grapevine can be affected by virus and virus-like diseases that may significantly reduce the productive life of the plants as well as the grape production in terms of the quantity and quality of the berries [ 1 ]. In fact, the grapevine has been described as the crop that hosts the largest number of plant viruses, with more than 85 viral species known to infect this important crop to date [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…After host genome subtraction 2. Grapevine fanleaf virus (GFLV); Grapevine fleck virus (GFkV); Grapevine leafroll-associated virus 1 (GLRaV-1); Grapevine leafroll-associated virus 2 (GLRaV-2); Grapevine leafroll-associated virus 3 (GLRaV-3); Grapevine red globe virus (GRGV); Grapevine rupestris vein feathering virus (GRVFV); Grapevine Syrah virus 1 (GSyV-1); Grapevine virus A (GVA); Grapevine virus B (GVB); Grapevine virus E (GVE); Grapevine virus F (GVF); Grapevine virus G (GVG); Grapevine virus L (GVL); Grapevine yellow speckle viroid-1 (GYSVd-1); Grapevine yellow speckle viroid-2 (GYSVd-2); Hop stunt viroid (HSVd); Grapevine rupestris stem pitting-associated virus 1 (RSPaV-1).…”
mentioning
confidence: 99%
“…High-throughput sequencing (HTS) revealed a multivirus infection of 'Syrah' grapevines with GRSPaV as the most prevalent (Al Rwahnih et al 2009). Also, an initial HTS conducted in several Australian vineyards showed that in grapevines affected by Shiraz disease, GRSPaV was commonly detected in combination with grapevine virus A (GVA) and some other viruses (Wu et al 2020). In general, GRSPaV causes asymptomatic or mild infections (Reynolds et al 1997); even beneficial effects, such as a greater resistance to initial levels of water stress, have been observed on 'Cabernet Sauvignon' grapevines (Gambino et al 2012).…”
mentioning
confidence: 99%
“…The Serbian GRSPaV sequence variants are underlined vineyards. GRSPaV has been predominantly detected in mixed infections (Sabella et al 2018;Wu et al 2020), but reports on individual infections are also available (Glasa et al 2017;Tobar et al 2020). Although foliar symptoms caused by GRSPaV are not observed on most commercial grapevine cultivars and the virus is reported to be mostly asymptomatic in single infections (Meng et al 2005), the GRSPaV detected in this study in 3-year-old 'Cabernet Sauvignon' grapevines was associated with weak growth and intensive reddening of the entire leaf blade.…”
mentioning
confidence: 99%